Parametric Study of Time-Dependent Corrosion Product Activity due to 56Mn, 58Co, and 60Co in the Primary Coolant Circuit of a Typical Pressurized Water Reactor - Muhammad Rafique; Nasir M. Mirza; Sikander M. Mirza; Kimberlee J. Kearfott; Shahab A. Abbasi; Syed F. Naeem (Journal of Chemistry)
Results of a detailed study, based on the parametric analysis of activated corrosion products, in primary coolant of a typical pressurized water reactor (PWR) are presented. The parameters influencing time dependent buildup of corrosion product activity (CPA) in primary coolant loop of PWR were identified. The computer program CPAIR was used to accommodate for time dependent corrosion rates. The behaviors of 56Mn, 58Co, and 60Co were studied over the reactor operational time. During the course of normal operation of reactor, the CPA is dominated by 56Mn, while 58Co and 60Co are the predominant radionuclides after reactor shutdown. Parametric study suggests that the total CPA is most sensitive to ion-exchanger removal rates. For a removal rate of 300 cm3-s−1, the specific activity due to 56Mn has the maximum value of 3.552 × 104 Bq-m−3 after 1,000 hours of reactor operation. This value decreases drastically to 8.325 × 103 Bq-m−3 at removal rate of 900 cm3-s−1. Additionally, CPA due to 56Mn, 58Co, and 60Co shows strong dependence on removal rates from the core material surfaces. Variations in the values of radionuclide removal rates from piping surface and radionuclide removal rate from deposition on pipes showed only very small effects on CPA buildup.